Perancangan Dinamometer Skala Kecil untuk Pengujian Karakteristik Gesek Bahan Blok Rem Kereta Api - Rizal Akhmad Bukhori; Eko Surojo; Nurul Muhayat (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
The brake blocks are components of the railway braking system that are useful for reducing speed or stopping the railway. In the development of railway brake block material needs a device that capable of testing the characteristics of the brake block material. One of the important characteristics of the brake block material is the frictional characteristic. The method of testing the frictional characteristics of existing brake blocks include using the pin on disc method, direct testing on the railway and using a full-scale dynamometer. The full-scale dynamometer has advantages than other methods because it can test specimens according to the actual railway braking conditions in a short time and less preparations. However, with the same specimen size as the original, the cost of making the specimen and the full-scale dynamometer become expensive. Therefore, to reduce the cost of making device and test specimens, this study will design the dynamometer small-scale brake block testing. This paper use Pahl and Beitz design method which divides the design into four stages: clarification of the task, conceptual design, embodiment design, and detail design. This dynamometer is designed by considering function designs, structures, and forces that are adapted to the brake block contact pressure according to the original conditions. This dynamometer is designed to vary material, wheel speed, and contact presssure with the output of measurement of friction coefficient of brake block material. Brake block test specimens have a reduced size with a 1: 4 scale from their original size. The results obtained from this research are engineering drawings and dynamometer test model of railway braking.